A Parallel Algorithm for Generating Maximal Interval Groups in Interval Databases Based on Schedule of Event Points - Arman, Nabil (My University, 2007)
In this study, a parallel algorithm to generate all maximal interval groups form a given interval set is presented. The algorithm makes use of intraoperation parallelism to speed up the generation of the maximal groups. The development of efficient algorithms to enumerate all intervals that have certain properties has attracted a large amount of research efforts due to the important role of interval-based reasoning in different areas like rule-based systems, including Expert Systems (ESs), Information Distribution Systems (IDSs) and database systems to name a few. These algorithms are very crucial to answer certain queries about these intervals.
Keywords: Maximal Interval Groups, Interval Databases, Parallel Databases